Analisis Proses Administrasi Pembukaan Rekening dalam Mendukung Efektivitas Pelayanan Nasabah Pada Bank BJB Syariah KCP UIN Sunan Gunung Djati - Widaningsih Widaningsih; Herry Sutanto (Journal of Economics, Management, and Accounting, 2026)
Account opening administrative process is one of the essential activities in banking operations as it relates to accurate customer data management and service quality. This study aims to analyze the account opening administrative process in supporting customer service effectiveness at Bank BJB Syariah KCP UIN Sunan Gunung Djati Bandung. This research employs a descriptive qualitative method with data collection techniques through observation and documentation during the Field Work Practice (PKL) program. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that the account opening administrative process is carried out through several stages, including form preparation, document completeness checking, customer data verification, approval process, and document archiving. The implementation of a structured administrative process has been proven to support service effectiveness by improving service speed, reducing administrative errors, and facilitating the overall customer service flow.